Norbin ablation results in defective adult hippocampal neurogenesis and depressive-like behavior in mice - Wang, Hong (Proc Natl Acad Sci U S A, 2015)
Adult neurogenesis in the hippocampus subgranular zone is associated with the etiology and treatment efficiency of depression. Factors that affect adult hippocampal neurogenesis have been shown to contribute to the neuropathology of depression. Glutamate, the major excitatory neurotransmitter, plays a critical role in different aspects of neurogenesis. Of the eight metabotropic glutamate receptors (mGluRs), mGluR5 is the most highly expressed in neural stem cells. We previously identified Norbin as a positive regulator of mGluR5 and showed that its expression promotes neurite outgrowth. In this study, we investigated the role of Norbin in adult neurogenesis and depressive-like behaviors using Norbin-deficient mice. We found that Norbin deletion significantly reduced hippocampal neurogenesis; specifically, the loss of Norbin impaired the proliferation and maturation of newborn neurons without affecting cell-fate specification of neural stem cells/neural progenitor cells (NSCs/NPCs). Norbin is highly expressed in the granular neurons in the dentate gyrus of the hippocampus, but it is undetectable in NSCs/NPCs or immature neurons, suggesting that the effect of Norbin on neurogenesis is likely caused by a nonautonomous niche effect. In support of this hypothesis, we found that the expression of a cell–cell contact gene, Desmoplakin, is greatly reduced in Norbin-deletion mice. Moreover, Norbin-KO mice show an increased immobility in the forced-swim test and the tail-suspension test and reduced sucrose preference compared with wild-type controls. Taken together, these results show that Norbin is a regulator of adult hippocampal neurogenesis and that its deletion causes depressive-like behaviors.